Differences of inter-canine distance on dental cast model, wax impression tracing, radiograph of dental impression tracing, and dental cast tracing methods of human bite mark - Fidya, Fidya; Swastirani, Astika (Padjadjaran Journal of Dentistry, 2019)
Introduction: Bite marks are unique to each, differing between one person and another. Several methods to analyse bite mark have been developed during certain periods. However, a standard method to analyse and evaluate the bite mark anatomic variations has not been developed. The objective of this research was to identify the differences of the inter-canine distance on dental cast model, wax impression tracing, radiograph of dental impression tracing, and dental cast tracing methods of the human bite mark. Methods: The subject of the research was as much as 30 consecutive dental cast model, wax impression tracing, radiograph of dental impression tracing, and dental cast tracing for both maxilla and mandible. Measurements performed on each group were conducted in the inter-canine areas using a Vernier calliper. The gold standard that used as a comparator was a dental cast model group on both maxilla and mandible. Comparison of the measurement results was carried out and analysed using a one-way ANOVA test and Tukey LSD test. Results: The average sizes of maxilla and mandible were 37.93 mm and 31.70 mm for dental cast model; 37.93 mm and 32.83 for wax impression tracing; 38.20 mm and 31.70 mm for radiograph dental impression tracing; and 36.65 mm and 30.76 mm of dental cast tracing. The significance value of the maxilla was p = 0.008 (p < 0.05), and the significance value of mandible was p = 0.000 (p < 0.05). Conclusion: The inter-canine distance of radiograph tracing group is found to be most similar with dental cast group as gold standard both in the maxilla and the mandible. Keywords: Bite mark, dental cast, wax impression, radiograph, tracing